The Salutations Used by Indonesian Society Through Comments on Social Media Platform TikTok - Noorapsari, Deby Triananda; Rokhman, Fathur; Mardikantoro, Hari Bakti (Universitas Negeri Semarang, 2023)
The salutations in TikTok comments exhibit diverse and unique forms that warrant exploration and study from a sociolinguistic perspective, utilizing components of speech. The aim of this research is to discern the various forms of salutations in TikTok comments, the variations thereof, and the factors influencing their creation. The research methodology employed is qualitative, analyzing textual fragments and comments perceived as forms of salutations within TikTok. Data sources comprise comments within the TikTok application, collected from March 3, 2023, to July 2023, totaling 42 instances. Data collection utilizes meticulous listening techniques, tabulated and subsequently clarified. Research findings elucidate speech events underlying the emergence of salutations diction in TikTok comments, predominantly among adolescents, particularly young women. The instrumentality of salutations is explicated within TikTok comment texts. Contributions of this research encompass analyses of salutations utilized in comments, revealing patterns of social interaction among TikTok users, offering insights into levels of respect and politeness conveyed through salutations, observing shifts in their usage, identifying potential new trends in salutations among TikTok users, and providing insights into the online behavior of Indonesian society.